Molecular Modeling Studies of Piperidine Derivatives as New Acetylcholinesterase Inhibitors against Neurodegenerative Diseases - Elaine F. F. da Cunha; José E. Resende; Tanos C. C. Franca; Mateus Aquino Gonçalves; Felipe R. de Souza; Letícia Santos-Garcia; Teodorico C. Ramalho (Journal of Chemistry)
Neurodegenerative disorders are related to the progressive loss of structure or function and, eventually, death of neurons. These processes are responsible for diseases like Parkinson’s, Alzheimer’s, and Huntington’s, and the main molecular target for the drug design against these illnesses today is the enzyme acetylcholinesterase (AChE). Following this line, in the present work, we applied docking techniques to study some piperidine derivative inhibitors of AChE and further propose structures of six new AChE inhibitors as potential new drugs against neurodegenerative disorders. The best inhibitor proposed was submitted to additional molecular dynamics simulations steps.